2020
DOI: 10.1371/journal.pmed.1003069
|View full text |Cite
|
Sign up to set email alerts
|

Health profile of pediatric Special Immigrant Visa holders arriving from Iraq and Afghanistan to the United States, 2009–2017: A cross-sectional analysis

Abstract: Background The United States has admitted over 80,000 Special Immigrant Visa holders (SIVH), which include children. Despite the increase in the proportion of SIVH admissions to the US over recent years, little is known about health conditions in SIV children. We report the frequency of selected diseases identified overseas and assess differences in selected conditions between SIV children from Iraq and Afghanistan. Methods and findings We analyzed 15,729 overseas medical exam data in Centers for Disease Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…A study conducted on recent arrivals of pediatric patients to the United States between 2009 and 2017, including refugees with Special Immigrant Visas from Afghanistan and Iraq, reported a higher prevalence of visual abnormalities, particularly among those from Iraq compared to those from Afghanistan. 32 This finding aligns with studies conducted on adult Syrian refugees in Philadelphia, where a higher prevalence of ocular diseases was observed. 7 , 8 It is essential to note that several studies have identified significant barriers experienced by vulnerable populations in the United States that have increased the likelihood of loss to follow-up (LTFU), including age greater than 65 years, having Medicaid insurance, having a lower income, and racial and ethnic demographic background.…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted on recent arrivals of pediatric patients to the United States between 2009 and 2017, including refugees with Special Immigrant Visas from Afghanistan and Iraq, reported a higher prevalence of visual abnormalities, particularly among those from Iraq compared to those from Afghanistan. 32 This finding aligns with studies conducted on adult Syrian refugees in Philadelphia, where a higher prevalence of ocular diseases was observed. 7 , 8 It is essential to note that several studies have identified significant barriers experienced by vulnerable populations in the United States that have increased the likelihood of loss to follow-up (LTFU), including age greater than 65 years, having Medicaid insurance, having a lower income, and racial and ethnic demographic background.…”
Section: Discussionsupporting
confidence: 87%
“…We can compare our ndings to published studies that describe the mental health patterns of MENA children using community-based samples. However, many of the existing studies report that MENA children have worse mental health than other racial/ethnic groups but are limited to speci c geographic regions in the US (e.g., Michigan, Minnesota) [18,19], nativity or ethnic origins (e.g., Iraqi, Syrian, Sudanese, Somalian) [18][19][20]. Our results differed from these studies which identi ed mental health concerns as worse among MENA children compared to other racial/ethnic groups, which may be due to sampling and how the variables were collected and conceptualized.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they reported that those refugees residing in the US for <15 years are about half as probable to have ever gone through CRC screening [ 21 ]. Since most Afghan refugees are not fluent in English, as their native language is either Pashto and Persian, we can predict that unfamiliarity with the English language presents an incredible difficulty in understanding the significance of CRC testing in this subset of refugees [ 22 ].…”
Section: Reviewmentioning
confidence: 99%